Pendapatan Usahatani Kelapa Di Desa Tumani Kecamatan Maesaan Kabupaten Minahasa Selatan - Tania, Nefaria Trifena; Lolowang, Tommy Fredy; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to determine the amount of coconut farming income in Tumani Village, Maesaan District, South Minahasa Regency. The research was conducted for 2 months from June to July 2023 in Tumani Village, Maesaan Subdistrict, South Minahasa Regency. The data concluded included primary data and secondary data. Farmer data collection was carried out using the simple random sampling method with the analysis method using income analysis. Coconut farming income in Tumani Village, Maesaan District, South Minahasa Regency with the sales method by selling copra gets a result of Rp6,760,918 per harvest which is obtained from total revenue of Rp9,279,700 per harvest minus the total cost of Rp2,518,782 per harvest and sales by selling coconut grains get a result of Rp2,557,546 per harvest which is obtained from total revenue of Rp3,876,600 per harvest minus the total cost of Rp1,322,176 per harvest.